Developing anxiety scale of writing thesis on students - Suryawati, Citra Tectona; Purwaningrum, Ribut; Susilo, Agus Tri (Universitas Islam Negeri Raden Intan Lampung, 2020)
The obligation to complete studies is one thing that must be experienced by a student. One of the obligations as a student in completing studies is the preparation of a thesis. This study aims to produce a thesis anxiety scale instrument for students which is a non-test instrument. This research is development research that uses three stages of development, namely preliminary research, prototyping stage and assessment phase. The subjects in this study were 131 students from 23 study programs in the Faculty of Education, Sebelas Maret University. The student anxiety instrument in the thesis developed three important indicators that affect anxiety, namely cognitive aspects, affective aspects and psychomotor aspects. Data analysis using the percentage of agreements and product moment analysis. The results of this study indicate that there are 29 items of thesis anxiety that are declared valid with a high level of reliability. Anxiety in writing this thesis greatly affects student performance and has an impact on the duration of thesis writing.